2012
DOI: 10.1099/jmm.0.043992-0
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite analysis of Candida isolates from recurrent vulvovaginal candidiasis

Abstract: Candida albicans and Candida glabrata are the most common causative agents of both vulvovaginal candidiasis (VVC) and recurrent vulvovaginal candidiasis (RVVC). Studying the population structure and genotype differentiation of Candida species that cause RVVC may lead to a significant improvement in clinical management. A total of 106 isolates were collected from 55 patients who were subdivided into three groups. Group I comprised 15 patients with RVVC (n550 isolates); group II comprised 16 patients, who had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
20
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 17 publications
6
20
2
Order By: Relevance
“…Analysis of the 225-12 and 402-12 isolate pairs showed that they have almost identical genotypes, confirming that only one strain was present in each of the patients during Candida infection. Moreover, the presence of isolates with minimal variation in all microsatellite loci suggests the occurrence of an adaptation to environmental conditions as part of a microevolution process, as previously described [34].…”
Section: Discussionsupporting
confidence: 68%
“…Analysis of the 225-12 and 402-12 isolate pairs showed that they have almost identical genotypes, confirming that only one strain was present in each of the patients during Candida infection. Moreover, the presence of isolates with minimal variation in all microsatellite loci suggests the occurrence of an adaptation to environmental conditions as part of a microevolution process, as previously described [34].…”
Section: Discussionsupporting
confidence: 68%
“…Candida albicans isolates contain many loci, and accordingly, several markers have been developed for them (16,19). However, it seems that most of microsatellites in coding regions have low levels of heterozygosity, although the use of multiplex PCR and the evaluation of more loci increase the discriminatory power (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…RAPD, is now considered by many to have suboptimal reproducibility and difficult to standardize (Table 3) [15]. In comparison, microsatellite analysis has the advantage of incorporating markers that evolve rapidly within the genome, offering good discriminatory power, reproducibility and portability, and is less costly [29, 30]. …”
Section: Discussionmentioning
confidence: 99%